Pengaruh Gaya Hidup, Kualitas Produk, dan Konten Pemasaran terhadap Keputusan Pembelian(Studi Kasus pada Pengguna Sepatu Ventela di Kota Bekasi) - Nawaal Amrullah; Indra Muis (Indo Publishing, 2026)
This study examines the influence of lifestyle, product quality, and marketing content on purchasing decisions for Ventela shoes in Bekasi City. The footwear industry in Indonesia has experienced rapid growth, with increasing competition between local and international brands. Ventela, as a local shoe brand, needs to understand the factors influencing consumer purchasing decisions. This quantitative research employs a survey method with questionnaires distributed to 120 Ventela shoe users in Bekasi City. Samples were determined using non-probability sampling with a combination of purposive and random sampling, with criteria of Ventela shoe users aged 14 to 29 years. Data were analyzed using IBM SPSS Statistics 27 through instrument testing, classical assumption tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination. The results show that lifestyle has a positive and significant effect on purchasing decisions (sig. 0.001), product quality has a positive and significant effect (sig. 0.000) and is the most dominant variable, and marketing content has a positive and significant effect (sig. 0.048). Simultaneously, all three variables significantly influence purchasing decisions (sig. 0.000) with an R Square of 0.531, meaning they explain 53.1% of purchasing decisions. This research contributes insights for Ventela to strengthen product quality as the main factor in improving purchasing decisions, while adapting products to consumer lifestyles and developing relevant, attractive, and informative marketing content.